Acute effects of ice hockey on hip range of motion, strength, and pelvic tilt in competitive male players - Suits, W. H.; O`Neil, M. M.; Fogarty, K. J. (Sports Health: A Multidisciplinary Approach, 2024)
Background: Ice hockey players are at high risk for hip and groin injury. Several risk factors have been identified or proposed, including lower hip rotation range of motion (ROM), lower hip adductor strength, lower ratio of hip adductor to abductor strength, and lower pelvic tilt angle. It is not known how these risk factors change acutely with ice hockey participation.